GDNF Schwann cells in hydrogel scaffolds promote regional axon regeneration, remyelination and functional improvement after spinal cord transection in rats. (26th June 2017) - Chen, Bingkun K.; Madigan, Nicolas N.; Hakim, Jeffrey S.; Dadsetan, Mahrokh; McMahon, Siobhan S.; Yaszemski, Michael J.; Windebank, Anthony J.
Abstract: Positively‐charged oligo[poly(ethylene glycol)fumarate] (OPF + ) is a biodegradable hydrogel used for spinal cord injury repair. We compared scaffolds containing primary Schwann cells (SCs) to scaffolds delivering SCs genetically modified to secrete high concentrations of glial cell‐derived neurotrophic factor (GDNF). Multichannel OPF + scaffolds loaded with SCs or GDNF‐SCs were implanted into transected rat spinal cords for 4 weeks. GDNF‐SCs promoted regeneration of more axons into OPF + scaffolds (2773.0 ± 396.0) than primary SC OPF + scaffolds (1666.0 ± 352.2) ( p = 0.0491). This increase was most significant in central and ventral‐midline channels of the scaffold. Axonal remyelination was quantitated by stereologic analysis. Increased myelination of regenerating axons was observed in the GDNF‐SC group. Myelinating cell and axon complexes were formed by host SCs and not by implanted cells or host oligodendrocytes. Fast Blue retrograde tracing studies determined the rostral‐caudal directionality of axonal growth. The number of neurons that projected axons rostrally through the GDNF‐SC scaffolds was higher (7929 ± 1670) than in animals with SC OPF + scaffolds (1069 ± 241.5) ( p < 0.0001). The majority of ascending axons were derived from neurons located more than 15 mm from the scaffold‐cord interface, and were identified to be lumbosacral intraspinal motor neurons. Transected animals with GDNF‐SC OPF + scaffolds partially recovered locomotor function at weeks 3 and 4 following surgery. Copyright © 2017 John Wiley & Sons, Ltd.